Firefighter neural function and decision-making following rapid heat stress. (December 2020) - Coehoorn, Cory J.; Stuart-Hill, Lynneth A.; Abimbola, Wande; Neary, J. Patrick; Krigolson, Olave E.
Abstract: In the present experiment we evaluated the impact of rapid heat stress on decision-making and neural function. Previous work has demonstrated that heat stress has an impact on cognitive and neural function. Here, we hypothesized that a rapid increase in heat stress would result in reduced decision-making ability evidenced by a reduction in frontal theta electroencephalographic (EEG) power. Fifteen participants performed an incremental exercise test to a termination criterion (volitional maximum, core temperature = 39.5 °C, or a 2-h time cap) with or without fire-fighting gear (selection was randomized) in a laboratory with an ambient temperature of 25–26 °C. Immediately following the exercise test, participants completed a Go/No-Go task and we observed an increase in incorrect responses when the subjects were wearing fire-fighting gear; no change was observed without gear. Additionally, an analysis of frontal EEG revealed a decrease in theta power when comparing pre- and post-exercise values with fire-fighting gear on; no change was observed without gear. Importantly, our results suggest that rapid heat stress and the resulting increase in physiological strain causes a decrease in cognitive control that could result in serious consequences in life-saving occupations that require contemplative, effortful decision-making.